Estimating saline water table contributions to crop water use - M Grismer; T Gates (California Agriculture, 1988)
Researchers in several western states have found that, under arid conditions, water tables can supply as much as 60 to 70 percent of a crop's water requirement. Use of high water tables reduces irrigation needs, lowers production costs, reduces deep seepage losses, and decreases the volume of drainage water requiring disposal. Successful use of the water table also depends on the soil's water retention and transmitting properties, evapotranspiration (ET) demand, distribution of the plant root system, and salinity and toxic ion effects on crop growth. Under field conditions, many of these factors are part of the overall crop response to the saline.